The nonlinear effects in the ionospheric plasma generated by strong thunderstorms seen by DEMETER satellite (Archives of Mechanics - Test, 2024)
The terrestrial ionosphere is mainly a plasma region which is very sensitive to different disturbances. A wide range of plasma instabilities can develop in this region, which are often nonlinear processes and leading to the development of plasma turbulence. Turbulence plays a crucial role in the dynamics of the space plasma processes. The turbulence appears when some physical parameter exceeds a certain level. It can have place during strong thunderstorms. The ionosphere is sometimes treated as plasma physics laboratory with unique possibility to study fundamental plasma processes. The use of ionospheric satellite gives the chance to perform insitu measurements of plasma parameters during dynamic processes. For our analysis we used a set of selected data of the electric and magnetic fields variations in ELF (Extra Low Frequency 10–1250 Hz) and VLF (Very Low Frequency 100–20000 Hz) ranges originated from the French microsatellite DEMETER which was operating on the circular orbit with inclination of about 80° at altitude of 660 km from July 2004 until December 2010. The Fourier, wavelet and bispectral analyses of these signals are given in this paper. Three wave processes have been identified during few very strong strokes. In some cases the nonlinear interactions of whistlers with the VLF signals of ground based transmitters have been registered. The character of spectra suggests the presence of Richardson’s cascade. Our conclusion is that in few cases these results are related to whistler turbulence.